Comment on the paper titled"Two-dimensional Sc2C: A reversible and high capacity hydrogen storage material predicted by first-principles calculations" by Hu et al., International Journal of Hydrogen Energy, 2014; 69, 1–4. (28th February 2020) - Santhosh, Archa; Ravindran, P.
Abstract: Hu et al. reported the hydrogen storage properties of Sc2 C and Ti2 C based MXene phases utilizing density functional theory (DFT) as implemented in the CASTEP code [1, 2]. Based on such calculations, the authors suggest that the MXenes should be a new family of potential hydrogen storage media. Their results claim a maximum hydrogen storage capacity of 9.0 wt% with an average binding energy of 0.164 eV/H2 in Sc2 C MXene indicating Kubas-type interaction between H2 and the MXene. These investigations are of prime importance since they provide insight about further applications of MXenes for hydrogen storage. In these calculations they have used local density approximation (LDA) to estimate the adsorption energies. However, binding energies for H2 with the MXene phases mentioned above obtained from more accurate calculations based on Generalised Gradient Approximation (GGA) and calculation including dispersion correction (GGA + vdW) show very weak binding energy ( ∼ 0.064 e V / H 2 ) suggesting weak physical interactions between H2 and the MXene phases. Our accurate DFT calculations predict that these MXene phases are not suitable for hydrogen storage at realistic conditions. So we conclude that appropriate exchange-correlation functional should be used to extract hydrogen adsorption energies in nano-phases to describe their hydrogen storage properties reliably.